Studi kasus analisis Business Process Management Notation untuk pesanan pembelian dan penerimaan barang pada usaha kecil menengah - Sulthan, Nafis; Jaswadi, Jaswadi; Sulistiono, Sugeng (Journal of Industrial Engineering & Management Research, 2021)
This research was aimed to analyze the business process of product purchase and product receipt on small and medium retail enterprises. The most of problem that appeared on Small and Medium Enterprises (SME) was lack of awareness to fix and improve the business process, because the appropriate business process could help the development of organization. The illustration of business process used Business Process Modeling Notation (BPMN). BPMN could really help the making of business process to be understood easier by the users and could be analyzed, so it produced improvement suggestions on the business process in order to achieve business effectiveness. This research was a qualitative research, which the research data was collected through observation and interview techniques in PO Dolopo Grosir which was one of the biggest wholesale shops in Madiun District. The research result referred the deficiency on the business process of product purchase and product receipt in PO Dolopo Grosir. The deficiencies on this business process could be risky to cause problems such as error of purchase decision, forgetfulness of product return, and less strict checking standard on product receipt process.